HIDDEN DEBT CHINA KE INDONESIA MASA PANDEMI COVID-19: TINJAUAN ATAS PERSPEKTIF STRUKTURALIS DAN RATIONAL CHOICE THEORY - Fuad Azmi; Emil Mahyudin; Gilang Nur Alam; RMT Nurhasan Affandi; Windy Dermawan (LPSDI Bina Patria, 2022)
Covid 19 has an impact on the world economic crisis which has brought the world to the brink of the worst economic recession in the last 50 years of world economic history. This causes the state to require debt to other countries, including Indonesia. Indonesia's state debt during the pandemic continued to grow so that it was accused of